A HYBRID MODEL OF SOLAR-WIND - BIOMASS POWER GENERATION SYSTEM (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
Renewable energy technologies offer the promise of clean, abundant energy gathered from self-renewing resources such as the sun, wind, water, earth, and plants. In this thesis a detailed modeling of hybrid power generation system of solar, wind and biomass has been developed in Matlab. The simulation includes all realistic components of the system. In this thesis, the power delivered by the combine system component is compared with each other and various conclusions are drawn. The various advantages and disadvantages of the system are compared, and a cost analysis of the system is carried on with the present system.